2014
DOI: 10.1039/c4cp00063c
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical synthesis of a gold atomic cluster–chitosan nanocomposite film modified gold electrode for ultra-trace determination of mercury

Abstract: Gold atomic cluster based nanocomposites are important in the field of energy and sensing applications due to their interesting optical, electronic, chemical and catalytic properties. In the present study a chitosan stabilized gold atomic cluster nanocomposite was synthesised by a simple electrochemical technique based on the anodic dissolution of a gold electrode in the presence of a cationic surfactant, cetyl trimethyl ammonium bromide (CTAB), and a biopolymer, chitosan, on a gold electrode. The gold cluster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 61 publications
0
8
0
1
Order By: Relevance
“…The detection of Hg 2+ and Cu 2+ ions is a frontier area of research in analytical chemistry and diverse colorimetric [45], fluorimetric [46] and electrochemical [47] techniques exist. What distinguishes the present study is the remarkable ability of the PPy solution to accomplish a qualitative detection and quantitative estimation.…”
Section: Selective Detection Of Metal Ions Using Ppy Solutionmentioning
confidence: 99%
“…The detection of Hg 2+ and Cu 2+ ions is a frontier area of research in analytical chemistry and diverse colorimetric [45], fluorimetric [46] and electrochemical [47] techniques exist. What distinguishes the present study is the remarkable ability of the PPy solution to accomplish a qualitative detection and quantitative estimation.…”
Section: Selective Detection Of Metal Ions Using Ppy Solutionmentioning
confidence: 99%
“…100 Aneesh et al 101 demonstrated the electrochemical synthesis of a gold atomic cluster-chitosan nanocomposite lm modied gold electrode for the ultra-trace determination of mercury over a wider calibration range of 1 fM to 0.1 mM with a limit of detection (LOD) of 0.8 fM. 100 Aneesh et al 101 demonstrated the electrochemical synthesis of a gold atomic cluster-chitosan nanocomposite lm modied gold electrode for the ultra-trace determination of mercury over a wider calibration range of 1 fM to 0.1 mM with a limit of detection (LOD) of 0.8 fM.…”
Section: Detection Of Heavy Metalsmentioning
confidence: 99%
“…Additionally, potential energy surface (PES) has also been scanned to have a clear inclination regarding the sensoranalyte binding fashion. Moreover, the reversibility of PMA in presence of F À /CN À and Hg 2 + (a toxic heavy metal which causes various fatal diseases, like Minamata disease) [18,[49][50][51][52][53] further incited to originate logic gate circuitry. In addition, a precise literature survey based on the F À and CN À selective chemosensors showed that most of the hitherto reported chemsoensors possess higher detection limit and lower binding constant in compared to PMA and the proposition towards logic gate imitator circuitry is less explored till now.…”
Section: Introductionmentioning
confidence: 99%